ECOLOGICAL STRUCTURE OF PLANT GROUPS OF KRYVYI RIH URBAN INDUSTRIAL COMPLEX (Ecological Bulletin of Kryvyi Rih District, 2021)
With the help of ecological and conomorphic analysis of vegetationusing the data “Ecoflora of Ukraine” according to the principles developedby O. L. Belgard (1960) found that in the plant groups of the Kryvyi Rihurban complex there are 74 species belonging to 63 genera and 22 families. Themost common members of such families as Asteraceae, Fabaceae, Brassic´aceae,Poaceae, Rosaceae, Apiaceae, Plantaginaceae, Salicaceae.The base of plant groups of the Kryvyi Rih urban-industrial complex iscreated by ruderants (51.27% of the total number of species) and stepants(21.61%). In addition, among the life forms according to the classificationK. Raunkier (1934) is dominated by hemicryptophytes (50% of the totalnumber of species) and therophytes (25.9%). In terms of preferences for waterregime, the most numerous are xeromesophytes (53% of the total number ofplants) and mesoxerophytes (29.4%). The groups are dominated by heliophytes(55.0%) and mesotrophs (60.6%).Ecological characteristics of the vegetation of research areas according to thesystem of ecomorphs O. L. Belgard (1950) found that the dominant positionamong coenomorphs belongs to ruderants (51.27% of the total number ofspecies) and steppes (21.61%). The sites in the Metallurgical District aredominated by ruderants and steppes.The climamorphic spectrum showed a quantitative predominance in thecomposition of plant groups of hemicryptophytes (50% of the total number ofspecies) and therophytes (25.9%). In general, all areas are dominated by plantsthat die at the beginning of the unfavorable period to ground level or surviveit exclusively in the form of seeds. This is one of the effective physiologicalmechanisms of preservation and increase in the number of species compositionin the areas.Analysis of hygromorphic spectra revealed the dominant role of transitionalforms from xerophytes to mesophytes. Xeromesophytes represent almost 53%of the total number of plants, and mesoxerophytes account for 29.4%. Thereare no xerophytes in plot 3.The number of heliophytes (55.0% of the total number of species) is thelargest among heliomorphs of all research sites. Among tropomorphs, the mostnumerous are mesotrophs (60.6% of the total number of species), megatrophsand oligotrophs are represented in equal numbers, namely 19%. Thus, the mostnumerous ecomorphs in the phytocenoses of research sites with different levelsof pollution are ruderants, hemicryptophytes, xeromesophytes, heliophytesand mesotrophs. Stepants, solvants, therophytes, mesophytes, megatrophs andoligotrophs have a stable presence.
Keywords: plant groups; industrial pollution; mining and metallurgical region; resistance